Rancang Bangun Multimedia Pembelajaran Interaktif pada Mata Kuliah Eletronika Menggunakan Adobe Flash CS 6 Berbasis RAD (Rapid Aplication Development) - Wahyu Hidayat; Nugroho Arif Sudibyo (Politeknosains, 2018)
This study aims to develop interactive multimedia learning products based on adobe flash CS 6 for electronics courses. Indonesia is a large country that has a very large population. The need for advanced technology is needed to assist the search for knowledge.One of the technologies used in teaching and learning systems is to use interactive multimedia using adobe flash CS 6. The method used in this research is the research and development method of Rapid Application Development (RAD). In Rapid Application Development (RAD) research model. which consists of 4 stages: (1) Requirement Planning, (2) Planning of Pseudo-Class Usage, (3) Construction of Pseudo Class (Construction), (4) Evaluation (Cut Over). The result of the research is interactive multimedia learning media using adobe flash CS 6 for electronics subject which can be reached by learners. This media can be used by learners and teachers to more interesting learners learn electronics.